Hydrogenated TiO2 Nanocrystals: A Novel Microwave Absorbing Material. (17th September 2013) - Xia, Ting; Zhang, Chi; Oyler, Nathan A.; Chen, Xiaobo
<x xml:space="preserve">Abstract</x> Here, we report, for the first time, hydrogenated TiO2 nanocrystals as a novel and exciting microwave absorbing material, based on an innovative collective‐movement‐of‐interfacial‐dipole mechanism which causes collective‐interfacial‐polarization‐amplified microwave absorption at the crystalline/disordered and anatase/rutile interfaces. This mechanism is intriguing and upon further exploration may trigger other new concepts and applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>